1995
DOI: 10.1289/ehp.95103s419
|View full text |Cite
|
Sign up to set email alerts
|

Vitellogenin induction by xenobiotic estrogens in the red-eared turtle and African clawed frog.

Abstract: Many environmental pollutants have estrogenic activity in animals. Xenobiotic estrogens include many pesticides and industrial chemicals that biocumulate. The impact of these common pollutants on the reproductive success of wildlife may be considerable, particularly in threatened or endangered species. This research examined the use of plasma vitellogenin in males as a biomarker for estrogenic xenobiotics in reptiles and amphibians. Adult male turtles (Trachemys scripta) and frogs (Xenopus laevis) were given i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
72
1

Year Published

1997
1997
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(77 citation statements)
references
References 58 publications
(58 reference statements)
4
72
1
Order By: Relevance
“…Indirect ELISA analysis of these samples again confirmed the immunoblot analysis (Fig. 5) (31,32). The sensitivity of Zrp cross-reaction demonstrated in this report points to the zona radiata proteins as a more sensitive biomarker for estrogenic effects of environmental pollutants.…”
Section: Methodssupporting
confidence: 77%
“…Indirect ELISA analysis of these samples again confirmed the immunoblot analysis (Fig. 5) (31,32). The sensitivity of Zrp cross-reaction demonstrated in this report points to the zona radiata proteins as a more sensitive biomarker for estrogenic effects of environmental pollutants.…”
Section: Methodssupporting
confidence: 77%
“…These observed hormone ratios indicate a strong demasculinizing effect from exposure to these chemicals. In a follow-up interview concerning this work, Hileman (347) (327) concluded that the vitellogenin assay may be a useful biomarker of xenobiotic estrogen activity in reptiles and amphibians in wild populations as well as fish. Palmer and Palmer (327) also noted that in the case of lipophilic compounds like o,p'-DDT, which have estrogenic activity and which also bioaccumulate, there may be negative impacts on fertilizability of eggs and development of embryos as these lipophilic contaminants are mobilized and transferred to sensitive tissues during the reproductive and developmental processes.…”
Section: Effects On Aquatic Life and Wildlifementioning
confidence: 99%
“…Unfortunately, the biomarkers used in those laboratory studies required sacrificing the individual for testing. For less-invasive field studies that require the survival of the animal, VTG has been proposed as a viable alternative, and its production has been induced in male herpetofauna at ecologically relevant doses of some pesticides (Palmer and Palmer, 1995;Brande-Lavridsen et al, 2008). However, on examining five previous studies, Rohr and McCoy (2010) found no effects on VTG production by atrazine.…”
Section: Vitellogenin and Sperm Screeningmentioning
confidence: 99%
“…Vitellogenin assays are used as a biomarker in fish to indicate exposure to estrogenic chemicals in the environment (Heppell et al, 1995). However, VTG production has been induced in the laboratory for several species of amphibians and reptiles (Palmer and Palmer, 1995). Vitellogenin assays are especially important for permanently aquatic salamanders that could be exposed throughout their lifetime and experience continuous exposure during the pesticide application season.…”
Section: Introductionmentioning
confidence: 99%